Financial Anxiety Among Caregiving Parents of Adult Children with a Substance Use Disorder - Rachel R. Tambling; Carissa D'Aniello; Beth Russell (Journal of Financial Therapy, 2021)
Substance use is a growing concern in the United States, with widespread harms, including substantial costs to individuals, families, and societies, poor outcomes for the substance user, and deleterious impacts on the family and community. When a young adult develops a substance use disorder, a parent or other loved one often assumes a caregiving role, and experiences burdens associated with this role including impacts to emotional well-being and financial stability. The present study examined experiences of financial anxiety in a sample (n = 172) of caregivers of adults with a substance use disorder recruited from online and in person treatment support groups. Regression analyses results indicated that caregivers experienced financial anxiety, and personal experiences of depression, as well as multiple treatment attempts not financially covered by insurance, contributed to reports of financial anxiety. Implications for families, family counselors, financial counselors, and substance use disorder treatment payers are discussed.
Keywords: Family finance; family studies; healthcare; financial stress; behavioral health; substance use disorders